Legal Responsibility And Environmental Impact Of Pollution By Pt Soedali Sejahtera In Pasuruan Regency, East Java - Suliyono, Aris (Fakultas Hukum Universitas Gresik, 2025)
This study aims to analyze the effect of the enforcement of administrative sanctions on the level of company This study discusses the legal responsibility and environmental impact of pollution carried out by PT Soedali Sejahtera, a textile company in Pasuruan Regency, East Java. This study is motivated by the fact that there are increasing cases of pollution in the textile industry in Indonesia which causes ecological, social, and economic losses. The research was conducted with a qualitative approach through the analysis of legal documents, community interviews, field observations, and laboratory tests on water quality. The analyzed parameters included BOD, COD, TSS, pH, and ammonia at three flow points (upstream, middle, downstream) in two different seasons. The results of the study showed a significant degradation of water quality, characterized by an increase in BOD and COD to exceed quality standards, a decrease in pH towards acidity, and an increase in ammonia levels that are potentially toxic to aquatic life. The socio-economic impact can be seen in declining agricultural productivity, increasing household clean water costs, and reduced consumer confidence in local products. From the legal aspect, the Surabaya District Court declared PT Soedali Sejahtera guilty and imposed damages of IDR 48.03 billion by applying the principle of strict liability and the principle of in dubio pro natura. This research emphasizes the importance of synergy between law enforcement, environmentally friendly technology, and community participation to realize ecological justice.